Accountable Preferences? Discourse, Identity, and the Anti-Prejudice Norm. (October 2016) - Stapleton, Karyn
There is, today, a powerful social norm against the expression of prejudice. Hence, as shown in many discursive studies, speakers treat prejudice as an accountable matter and use various strategies (e.g., disclaimers, mitigation, denials, and reformulations) to avoid being seen as personally prejudiced. Analysts have identified this practice as a "new" form of discriminatory discourse, which allows expression of prejudice without negative identity repercussions. Relevant studies are generally undertaken from a critical perspective and focus on structural inequalities (particularly race and gender). However, speakers may also demonstrate sensitivity around unexpected issues which lack overt prejudice connotations. This article examines one such example of unexpected sensitivity to the anti-prejudice norm. It analyses how five young female academics problematise and resolve their preference for an "intelligent" romantic partner. Their preference is uncontroversial in relationship terms, but here, in the academic context, it is clearly treated as accountable and as possibly inviting negative attributions. The data show functional and lexical features of "new" discriminatory discourse. The speakers orient towards attributions of intellectual elitism and use various means to deflect these, while ultimately upholding their stated preference for an intelligent partner. The analysis demonstrates how the anti-prejudice norm extends across settings/topics and how accountability is occasioned and context specific. This has implications for how prejudice itself, as a discursive construct, may be identified and evidenced. Specifically, it might be argued that analysts only have empirical access to accountability (occasioned in specific contexts), rather than to exclusionary or prejudiced ideologies per se.